EFEKTIVITAS KONSELING REALITA UNTUK MENGURANGI PERILAKU PROKRASTINASI AKADEMIK MAHASISWA - Batubara, Juliana (Fakultas Tarbiyah dan Keguruan UIN Imam Bonjol Padang, 2015)
Student learning activities need to be developed. One learning activity / learning activities a student is working on a task and collect assignments on time. However, conditions on the ground are less student exhibit behaviors that support learning activities well is procrastinating in doing so late in collecting duties. It is often termed academic procrastination. One technique that can help reduce the behavior of student academic procrastination is through counseling reality. In this reality counseling counselees should be able to be responsible for himself and abstain from unhealthy behaviors, namely behaviors that tend to ignore the principles of the 3Rs, namely Right, Reality and Responsibility.